2012
DOI: 10.1155/2012/251482
|View full text |Cite
|
Sign up to set email alerts
|

Protegrin-1 Inhibits Dengue NS2B-NS3 Serine Protease and Viral Replication in MK2 Cells

Abstract: Dengue diseases have an economic as well as social burden worldwide. In this study, the antiviral activity of protegrin-1 (PG-1, RGGRLCYCRRRFCVCVGR) peptide towards dengue NS2B-NS3pro and viral replication in Rhesus monkey kidney (MK2) cells was investigated. The peptide PG-1 was synthesized by solid-phase peptide synthesis, and disulphide bonds formation followed by peptide purification was confirmed by LC-MS and RPHPLC. Dengue NS2B-NS3pro was produced as a single-chain recombinant protein in E. coli. The NS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…Besides, the data of this study also confirmed our previous findings of the inhibition potential of PG1, PLSN against dengue virus replication [13], [16]. It has been shown that these peptides exhibited similar antiviral activities against different viruses.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, the data of this study also confirmed our previous findings of the inhibition potential of PG1, PLSN against dengue virus replication [13], [16]. It has been shown that these peptides exhibited similar antiviral activities against different viruses.…”
Section: Discussionsupporting
confidence: 90%
“…To date, several DENV proteases have been identified as potential targets for the discovery of anti-DENV inhibitors, including NS2B/NS3, NS4B and NS5 [49][50][51] , and the NS2B/NS3 protease is particularly important because of its essential role in the replication of DENV [52] . In fact, an inhibition strategy involving the protease complex and facilitated by a co-factor enzyme has been successfully applied in the discovery of antiviral drugs against human immunodeficiency virus (HIV) and hepatitis C virus (HCV) [53] , and several inhibitors targeting the HCV NS3/4A protease have already entered into clinical trials [54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…The activity of recombinant NS2B-NS3pro was measured by a fluorescence-labelled substrate as previously described [23,27]. The function of dengue protease depends on the binding between NS2B and NS3pro to form NS2B-NS3pro complex.…”
Section: Discussionmentioning
confidence: 99%
“…The bioassay used in this study was published by Rothan and co-workers [23]. In brief, endpoint reaction mixtures with total volume of 200 μl were prepared consisted of 20 μM fluorogenic peptide substrate (Boc-Gly-Arg-Arg-AMC), 2 μM of recombinant NS2B-NS3pro, with or without RC-1 of varying concentrations, buffered at pH 8.5 with 200 mM Tris–HCl.…”
Section: Methodsmentioning
confidence: 99%